Laboratory investigation and evaluation of the hydraulic fracturing of marine shale considering multiple geological and engineering factors - Wang, Lei; Zhou, Jun; Guo, Yintong; Song, Xuehang; Guo, Wuhao (Frontiers in Earth Science, 2022)
Hydraulic fracturing is widely implemented in the exploration of marine shale gas. Affected by various geological and engineering factors, gas production after stimulation is not always satisfactory. To reveal the influential effect of multiple factors, laboratory hydraulic fracturing experiments are performed on Longmaxi marine shale by considering key parameters (deviatoric stress, confining pressure, pumping rate, fracturing fluid type, and bedding angle). The variation of breakdown pressures and the characteristics of hydraulic fractures are recorded and analysed. The results show that the breakdown pressure increases with increasing deviatoric stress, confining pressure, pumping rate, and viscosity of the fracturing fluid. As the bedding angle varies from 0° to 90°, the breakdown pressure declines first and increases again. Further parameter sensitivity analysis indicates that geological factors (confining pressure, bedding angle, deviatoric stress) would largely determine the breakdown pressure, while engineering factors (pumping rate, fracturing fluid type) could only affect it to a lesser extent. Computed tomography measurements show that natural fractures, originating from tectonic shear failure, could possess greater width than tension-dominated hydraulic and bedding fractures. Statistical analysis shows that the length of hydraulic fractures alone is only approximately 150 mm. However, the fully activated natural and/or bedding fractures could help substantially increase the total fracture length to 600 mm. Low deviatoric stress, low confining pressure, low viscous slick-water, and high bedding angle are conducive to activating natural and bedding fractures and forming a complex fracture network. The above findings are valuable for the optimal design of field hydraulic fracturing.